Noise Mapping Pada PT. Makanan Olahan di Kawasan Ngoro Industri Persada (NIP) Dengan Menggunakan Surfer - Restu Hikmah Ayu Murti; Dinda Putri Sriweni (Prosiding ESEC, 2023)
With the production activities carried out by PT. Processed food has the potential for noise originating from the use of machines in both indoor and outdoor areas. This study aims to analyze potential noise levels, map the distribution of noise levels, and make efforts to mitigate the effects of potential noise levels at company locations. Determination of noise measurement points is carried out in the activity area of the machine then measuring noise using a Sound Level Meter at each point and the data obtained refers to Permenaker Number 5 of 2018 and Minister of Environment Decree No. KEP-48/MENLH/LH/11/1996. Mapping the distribution of noise levels using surfur software and the results of this study there are 3 noise levels. First, it ranges from 60-70 dBa, which means that the noise level is still within the quality standards of Permenaker Number 5 of 2018 and Minister of Environment Decree No. KEP-48/MENLH/LH/11/1996. Second, around 70-80 dB the noise level tends to be moderate and requires risk control in the form of planting trees of at least 75 cm for outside areas. Third, it ranges from 80-90 dB, which means that the noise level in this area tends to be high and requires risk control in the form of using earplugs or earmuffs for workers in that area. With Noise Mapping it is very useful for companies to reduce the level of risk of work accidents and increase comfort in the scope of the company